The Influence of Ownership Structure, Board Composition and Financing Decisions on the Performance of Manufacturing Companies in the Consumer Goods Sector - Pradana, Firmansyah Adhitya; Dabo, Mia El; Ricardo, Wilson; Lestari, Henny Setyo; Margaretha, Farah (SENTRALISASI, 2024)
This research aims to investigate the impact of ownership structure, board size, proportion of independent directors, funding decisions, company size, and dividend policy on the performance of consumer goods manufacturing companies. Purposive sampling was employed for data collection. Results indicate that ownership structure and board size positively and significantly influence company performance, as measured by Tobin's Q and ROA. However, the proportion of independent directors, funding decisions, company size, and dividend policy do not exhibit significant effects. Consequently, effective management of ownership structure and board size is crucial for enhancing company performance in the consumer goods manufacturing sector. These findings provide valuable insights for companies to improve their performance and corporate governance practices, fostering stability and sustainability in alignment with economic trends.